Geodynamic conditions for Cenozoic activation of tectonic structures in Southeastern Mongolia - A. V. Parfeevets; V. A. Sankov (Геодинамика и тектонофизика)
The knowledge of the neotectonic structures inSoutheastern Mongolia, that is considerably distant from the active plate boundaries, is important for determining a source of tectonic deformation and regular features of activation in the intracontinental setting. Our research was focused on the East Gobi and South Gobi depressions located inSoutheastern Mongolia, which developed since the Mesozoic and were activated to various degrees in the neotectonic stage. The study aimed to assess the paleostress state of the crust inSoutheastern Mongolia, identify the stages, factors and mechanisms of the Cenozoic activation of the regional structures of different strike, and determine the sources of activation. The analysis of the available literature suggests a similar history of their development in the Late Jurassic – Early Cretaceous (rifting) and Late Cretaceous – Paleogene (tectonic quiescence). In the Cenozoic stage, the depressions experienced activation of completely different styles. In theEast Gobidepression, left-lateral strike-slip faults were activated in the Tertiary, and the post-Late Cretaceous thrusting took place along the northeastern faults on the northern slope of the Totoshan uplift. In the Early Cenozoic, the N-S and N-W compression was dominant as evidenced by the deformed Late Cretaceous sediments and the reconstructed stress tensors typical of the compression and transpression regimes. An overview of the published data suggests that the most probable cause of such deformation was the impact of the Western Pacific zone of plate interaction. However, a potential influence of compression at the early stages of the Indo-Asian collision cannot be completely excluded. TheEast Gobidepression was low active in the second half of the Cenozoic. In contrast to the East Gobi depression, theSouth Gobiactivation began in the Late Cenozoic (Late Miocene – Early Pliocene). Young uplifts and forbergs (Gobi Altai eastern termination) developed actively and ‘cut’ the sediments of the basins originating from the Mesozoic. The W-E and N-W strike-slip and thrust faults were active in the Pliocene–Quaternary. The stress field reconstructions show compression, transpression and strike-slip regimes with the NE-trending axis of compression. Deformation in the East Goby Altay (as well as in Western andSouthwestern Mongolia) is driven by the India-Eurasia collision.